Problems with Application of Japanese Management in the Czech Republic - Jankotová, Petra (2008)
This graduation thesis' aim is to help reader realize and understand what makes Japanese companies, especially Japanese management style, so successful and competitive and what problems (challenges) may occur while applying the Japanese managerial techniques in the Czech Republic. Companies teaching and implementing Japanese managerial style were found and evaluated. While giving background information on Japanese economy and manners, basic description of chosen Japanese managerial techniques as well as examples of their usage in companies, the main idea is to find out what the prerequisites of successful implementation of Japanese managerial techniques are, how techniques can be implemented and consecutively describe possible obstacles at the application of the Japanese management in the companies outside Japan. The reason for looking for the prerequisites of successful implementation is the thought that not only managerial techniques themselves (their "technical side") are the key for success. It is also, and very importantly, the way how they are used. It is knowledge what "forces" are driving the success of the techniques. Therefore, in order to understand what the Japanese managerial techniques are and who the people developing and using them are about, I step by step gathered related information and in a summarized form wrote them in this thesis. Analyzing the information I was able to conclude that there are three prerequisites for successful implementation of Japanese managerial techniques. It is firstly a technical side of managerial techniques itself, secondly it is a psychological aspect (learning Japanese management also means learning pieces of Japanese culture and manners and only if that culture is understood and applied, techniques can show they full potential) and thirdly it is hard working.